Over-barrier ionization of hydrogen atom in intense circular and elliptical laser fields - Wang, Jiguo; Guo, Zhenning; Fang, Yiqi; Yu, Xiaoyang; Liu, Yunquan (Frontiers in Physics, 2022)
We investigate the over-barrier ionization of hydrogen atoms in intense circularly and elliptically polarized laser fields. By solving the time-dependent Schrödinger equation, we simulate the photoelectron momentum distributions with the peak laser field intensity ranging from tunneling ionization to over-barrier ionization regime. It is shown that the photoelectron momentum distributions reveal a spiral distribution in the over-barrier ionization regime, which is in contrast with the typical donut distribution sculpted by above-threshold ionization peaks in the tunneling ionization regime. To analyze the intriguing photoelectron behavior, we further develop a semi-classical model by considering the non-adiabatic effect and the depletion effect of the ground state. The photoelectron momentum distributions calculated by the semi-classical model agree well with the results of the time-dependent Schrödinger equation. Based on these results, we further explore the relationship between the instantaneous ionization rate and initial transverse momentum in over-barrier ionization. It is worth noting that such a relationship is not easy to be clearly revealed in tunneling ionization regime as the final electron momentum is significantly modified by the inter-cycle interference. Moreover, we also show that the non-adiabatic effect and long-range Coulomb interaction play important roles in the over-barrier ionization.